DAMPAK PELAKSANAAN MODEL MATEMATIKA REALISTIS PADA PENINGKATAN KEMAMPUAN PENALARAN DEDUKTIF SISWA SEKOLAH MENENGAH DI PARUNG KABUPATEN - KABUPATEN BOGOR - M.Si., Dr. Yumiati; Tarhadi, Tarhadi (LPPM Universitas Terbuka, 2010)
This study attemps to determine impact of the implementation of Realistic Mathematics Education (RME) model on the improvement of deductive reasoning ability, and to describe the perceptions of teachers and students of secondary schools toward the RME model. A quasi-experiment with pretest-postest non-equivalent group as research design was employed into 2 groups of research subject: the experimental group and the control group and each was treated under RME and conventional teaching model. A number of 44 students of SMPN1 Parung and 20 students of SMP Islam Terpadu Jabon Mekar in Parung District were chosen as research subjects. Quantitative data obtained through questionnaires and written tests were analyzed using Student-t test. While qualitative information gathered through responses to personal interview and observations was analyzed using qualitative-naturalistics method. Findings reveals that learning mathematics using the RME model impacts on increasing students deductive learning ability in both schools with amount of increase is 30.7 for SMP Islam Terpadu and 44.8 for SMPN1 Parung. RME model also impacts on developing students positive attitude of students toward mathematics as seen in the number of students who liked mathematics lesson, that is 100% for SMP Islam Terpadu and 97% SMPN 1 Parung. The perceptions of teachers and students in both schools toward the RME Model are positive. Application of learning mathematics using PMR model becomes more enjoyable and students become more active.